Differences in Physical Fitness, Quality of Life and Level of Physical Activity Among Adolescents Based on BMI: An Observational Study - Stefan Stojanovic; Tamara Ilić; Tijana Purenović-Ivanović; Doroteja Rančić; Ismail Ibak; Ana Lilic; Stefan Mijalković; Goran Prebeg (Journal of Anthropology of Sport and Physical Education, 2025)
Adolescence is an important transitional phase in life, central in the development of capabilities related to health and well-being, and where future patterns of adult health are established. Overweight and obese adolescents are at a higher risk of developing many chronic non-communicable diseases. Moreover, overweight and obesity negatively impact physical fitness (PF), quality of life (QoL) and levels of physical activity (PA). In this context, the aim of this study was to examine differences in PF, QoL, and PA level among adolescents based on BMI. The sample consisted of one hundred thirthy-nine (N=139) high school graduates (4th grade, aged 18 years, 43.7% girls). The Eurofit Fitness Test Battery was used to assess PF, whereas QoL questionnaire adolescent form and PA questionnaire (IPAQ-SF) were employed for QoL and PA level, respectively. One-way ANOVA and Tukey posthoc were conducted for comparisons (p<0.05). Main findings of this study indicate that there were significant differences among three groups (underweight, normal weight, overweight) in PF, QoL, and physical activity levels among adolescents (p<0.05; 0.03; 0.01, respectively) in favour of normal weight group. In conlusion, adolescents who are normal weight tend to have better PF, QoL and PA level in comparison with adolescents who are underweight and overweight. Those results underline the importance of spreading awareness about the harmfulness of an increased BMI (body mass index), i.e., the trend of increasing obesity in today's society.